Presença pentecostal numa sociedade de transição rural-urbana: a Igreja Pentecostal Chegada de Cristo e Curas Divinas estudo de caso - Chaves, Alexandre da Silva (2011)
This paper seeks to understand the Pentecostal religion in its historical-cultural perspective, considering both aspects to the transition of rural-urban municipality of Franco da Rocha. There is the possibility of studying the arrival of Christ Pentecostal Church and the causes of integration and accommodation in this rural region. On can observe that there is a reverse movement carried out over most of the Brazilian Evangelical churches, which would integrate the layers of urban society, however, research studies indicate that this church is trying in a rural context of transition. This paper presents Pentecostalism in Brazilian culture in its diverse forms of expression, based on case study presented in the context of the rural municipality of Franco da Rocha, it is observed how the culture in its broader aspect is politics, economics or history, a Pentecostal religiosity influences the everyday life that is transformed by this community. The survey notes a kind of evangelical Pentecostal which is beyond the routine aspect presented in the arena of urban religions. It is observed that the accommodation of the Pentecostal religion in an atmosphere of tradition and a rural context, culture configures a different kind of Pentecost in its spectrum, a type of Pentecostalism done mixing, which differs from the types of "Pentecostalism" in existing urban centers.